Diversity of Aquatic Fauna in Upper and Middle Tamor River and Possible Impacts of Hydropower Dam in Taplejung, Nepal - Thapa, Ganesh Bahadur (Himalayan Journal of Science and Technology, 2017)
Abstract on full text PDF.